Can measurement of maternal anti‐cytomegalovirus immunoglobulin‐M antibody levels be used to screen for cytomegalovirus infection in embryos and fetuses?. Issue 1 (4th June 2012) - Yoshida, Masashi; Matsuda, Hideo; Yoshinaga, Yosuke; Asai, Kazuhiko; Kawashima, Akihiro; Sei, Kiguna; Furuya, Kenichi
Abstract Aims: Our study aims to estimate whether measurement of maternal anti‐cytomegalovirus immunoglobulin‐M antibody (CMV‐IgM) levels are useful as a screening method for achieving early detection of congenital CMV infection. Material and Methods: Levels of maternal CMV‐IgM were measured by enzyme immunoassay in all (n = 2865) pregnant women who visited our hospital in the first trimester during the period from January 2005 to December 2009. Results: Among them, 21 individuals (0.73%) had a CMV‐IgM titer of ≥0.08 and were judged to be CMV‐IgM‐positive. Informed consent was obtained from all 21 individuals to perform the confirmation test that quantifies the levels of cytomegalovirus DNA (CMV‐DNA) in amniotic fluid by real‐time polymerase chain reaction. However, only one (0.03%) of the 21 individuals was CMV‐DNA‐positive (CMV‐DNA concentration, 1.0 × 104 copies/ml). Conclusion: In order to detect congenital CMV infection in early pregnancy, it is considered appropriate to use ultrasound for close examination of embryo or fetal symptoms indicative of CMV instead of performing serological screening based on CMV‐IgM.